2000
DOI: 10.1046/j.1439-0507.2000.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of bovine lactoferrin for treatment of tinea pedis. A placebo‐controlled, double‐blind study

Abstract: A clinical study was conducted to evaluate the effectiveness of lactoferrin, which is a protein component of cow's milk, in the treatment of tinea pedis. Doses of either 600 mg or 2000 mg of lactoferrin, or a placebo was orally administered daily for 8 weeks to 37 adults who were judged to have mild or moderate tinea pedis. Dermatological improvement and antifungal efficacy were assessed. In the analysis of all subjects, dermatological symptoms scores in all groups decreased but the differences were not statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…LF has a number of biological functions, including antimicrobial and immunomodulatory effects in vitro and in vivo (Brock, 1995;Tomita et al, 2002;Vorland, 1999). It has been reported that orally administered bovine LF reduces the number of pathogenic organisms not only in the gastrointestinal tract (Teraguchi et al, 1995;Wada et al, 1999) but also in tissues distant from the gastrointestinal tract in several animal models of infection (Abe et al, 2000;Bhimani et al, 1999;Haversen et al, 2000) and in humans with chronic hepatitis C and tinea pedis (Ishii et al, 2003;Iwasa et al, 2002;Yamauchi et al, 2000). It is known that LF and an LF-derived antimicrobial peptide, lactoferricin B (LFcin B), inhibit in vitro growth of fungi such as Candida albicans (Kuipers et al, 1999;Wakabayashi et al, 1996Wakabayashi et al, , 1998 and Trichophyton mentagrophytes ; it has been shown that orally administered LF shows a host-protective effect against systemic C. albicans infection in mice (Abe et al, 2000) and cutaneous T. mentagrophytes infection in guinea pigs .…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly appreciated that oral administration of LF or its fragment peptides improves the survival rate and enhances elimination of pathogens from the body of animals or human patients infected with bacteria, fungi, protozoa or viruses [3][4][5][6][7]. Recent studies showed that feeding bovine LF enhances the elimination of pathogens and the rate of symptomatic cure in guinea-pigs and man with dermatophytosis, a very common fungal infection on the skin [8,9]. LF exhibits in-vitro growth-inhibitory activity against the dermatophytes Trichophyton mentagrophytes and T. rubrum, causative fungi of dermatophytosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…11) Beneficial effects of orally administered bLF on infections and iron status have also been recently demonstrated in clinical trials in human adults and infants. [12][13][14][15] It has been reported from an in vitro study that brush border membranes prepared from human fetal small intestine showed higher affinity to hLF compared to bLF. 16) Binding of IntL to LF has been demonstrated only in a combination of receptors and ligands of human origin.…”
mentioning
confidence: 99%